Quality engineering design and construction in Malaysia: A fast disappearing and endangered commodity - Chiang, Jeffrey Choong Luin, Ir. Assoc. Prof. Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s home page at http://www.myiem.org.my/